On the electoral punishment/rewarding of the incumbent -- Can voters do it? - Caleiro, António Bento (2019)
The article analyzes the possibility of voters penalizing or rewarding the incumbent (economic) performance at the polls. For this, it is considered that voters have limited rationality. This does not prevent them from performing this task without bias, which should serve as an obligation to use the elections to effectively penalize or reward the incumbent and/or not elect those who do not deserve it.